Theory and computational study of electrophoretic ion separation and focusing in microfluidic channels - Klymenko, Oleksiy V. V.; Amatore, Christian; Sun, Wen; Zhou, Yong-Liang; Tian, Zhao-Wu; Svir, Irina (Nonlinear Analysis: Modelling and Control, 2012)
In this work we describe the theory and 2D simulation of ion separation and focusing in a new concept of microfluidic separation device. The principle of the method of ion focusing is classical in the sense that it consists in opposing a hydrodynamic transport ensured by the solution flow to an electrophoretic driving force so that any ionic sample results poised within the microchannel at the point where the two forces equilibrate. The originality of the concept investigated here relies on the fact that thanks to the use of an ion-conducting membrane of variable thickness in electrical contact with the channel the electrophoretic force is varied continuously all along the channel length. Similarly, changing the geometric shape of the membrane allows a facile optimization of the device separation and focusing properties.
Keywords: electrophoresis; analytical separation; ion-conducting membranes; 2D simulation